Evaluasi Keadilan Dalam Kebijakan Perpanjangan Masa Jabatan Kepala Desa: Pendekatan Normatif Sila Kelima Pancasila - Jannah, Laillatul; Sunaryo, Sidik (Innovative: Journal Of Social Science Research, 2025)
The extension of village head tenure from six to eight years in Law No. 3 of 2024 creates a paradox between administrative efficiency and the implementation of Pancasila's social justice values. This research aims to analyze the policy's consistency with the fifth principle of Pancasila's social justice, formulate evaluation parameters based on Pancasila values, and develop just policy formulations. A qualitative method with normative juridical approach was employed through library research and legal hermeneutic analysis of primary and secondary legal materials from 2020-2025. Results indicate that this policy potentially creates structural tensions in village democracy systems, with possible power accumulation up to sixteen years contradicting the principle of power limitation. Distributive and procedural justice analysis indicates the need for strengthened accountability and transparency mechanisms. The research concludes that policy implementation requires a holistic approach integrating governmental stability with democratization principles and inclusive community participation to ensure the achievement of social justice according to Pancasila's mandate.